2022
DOI: 10.1155/2022/1053484
|View full text |Cite
|
Sign up to set email alerts
|

On the Studies of Dendrimers via Connection-Based Molecular Descriptors

Abstract: Topological indices (TIs) have been utilized widely to characterize and model the chemical structures of various molecular compounds such as dendrimers, neural networks, and nanotubes. Dendrimers are extraordinarily comprehensible, globular, artificially synthesized polymers with a structure of frequently branched units. A mathematical approach to characterize the molecular structures by manipulating the topological techniques, including numerical graphs invariants is the present-day line of research in chemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Further, Liu et al [25] found the topological properties of neural networks. Recently, Sattar et al [26][27][28] worked on computing the general expression of ZIs for two types of dendrimers. For the other terminologies not discussed in this paper, the readers are referred to [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Further, Liu et al [25] found the topological properties of neural networks. Recently, Sattar et al [26][27][28] worked on computing the general expression of ZIs for two types of dendrimers. For the other terminologies not discussed in this paper, the readers are referred to [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Computation of entropy measures and valency-based indices of networks are discussed in [24] and [25]. The results of connection based such indices of networks are given in [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Cao et al [23] computed ZCIs of molecular graphs. Sattar et al [24][25][26] just discovered the CBZIs of dendrimer nanostars. Further, Ali et al [27] estimated modified CBZIs for T-sum graphs in 2020.…”
Section: Introductionmentioning
confidence: 99%